An advanced IoT system for monitoring and analysing chosen power quality parameters in micro-grid solution - Ngô Minh Khoa; Lê Văn Đại; Đoàn Đức Tùng; Nguyễn An Toàn (My University, 2021)
An advanced IoT system for monitoring and analysing chosen power quality parameters in micro-grid solution
Keywords: Power quality; Micro-grid; IoT system